Cardiopulmonary Exercise Testing in Patients Following Massive and Submassive Pulmonary Embolism. Issue 5 (3rd March 2018) - Albaghdadi, Mazen S.; Dudzinski, David M.; Giordano, Nicholas; Kabrhel, Christopher; Ghoshhajra, Brian; Jaff, Michael R.; Weinberg, Ido; Baggish, Aaron
Abstract : Background: Little data exist regarding the functional capacity of patients following acute pulmonary embolism. We sought to characterize the natural history of symptom burden, right ventricular (RV) structure and function, and exercise capacity among survivors of massive and submassive pulmonary embolism. Methods and Results: Survivors of submassive or massive pulmonary embolism (n=20, age 57±13.3 years, 8/20 female) underwent clinical evaluation, transthoracic echocardiography, and cardiopulmonary exercise testing at 1 and 6 months following hospital discharge. At 1 month, 9/20 (45%) patients had New York Heart Association II or greater symptoms, 13/20 (65%) demonstrated either persistent RV dilation or systolic dysfunction, and 14/20 (70%) had objective exercise impairment as defined by a peak oxygen consumption ( V ˙ O2 ) of <80% of age‐sex predicted maximal values (16.25 [13.4–20.98] mL/kg per minute). At 6 months, no appreciable improvements in symptom severity, RV structure or function, and peak V ˙ O2 (17.45 [14.08–22.48] mL/kg per minute, P =NS) were observed. No patients demonstrated an exercise limitation attributable to either RV/pulmonary vascular coupling, as defined by a VE/VCO2 slope >33, or a pulmonary mechanical limit to exercise at either time point. Similarly, persistent RV dilation or dysfunction was not significantly related to symptom burden or peak V ˙ O2 at either time point. Conclusions: Persistent symptoms, abnormalities of RV structure and function, and objective exercise limitation are common among survivors of massive and submassive pulmonary embolism. Functional impairment appears to be attributable to general deconditioning rather than intrinsic cardiopulmonary limitation, suggesting an important role for prescribed exercise rehabilitation as a means toward improved patient outcomes and quality of life.